Research on high-precision measuring technology of gear grinder based on the consideration of machine tool thermal error and probe pre-travel error - Yang, Yongming; Wang, Zhonghou; Kubo, Aizoh (International journal of advanced manufacturing technology, 2024)
Aiming at the problem that machine tool thermal error (MTE) and probe pre-travel error (PPE) seriously weaken measuring accuracy, existing researches are conducted under certain conditions that MTE in a constant ambient temperature is considered or only PPE is compensated. A novel comprehensive error MTE-PPE model with consideration of different constant ambient temperatures is developed to enhance measuring accuracy. Independently developed new type of horizontal CNC gear grinder (L300G) regarded as the research object, MTE-PPE is equivalent to probe slip error (PSE) based on involute property and L300G involute gear measuring principle. Mini-batch gradient descent optimization algorithm (MGDOA) is employed to reckon more reasonable PSE compensation values, on the basis of which grinded topological modification tooth surface is fitted according to the least squares method (LSM) tooth surface fitting principle. The theoretical topological modification tooth surface is constructed founded on the L300G involute helical gear topological modification grinding principle, and morphology deviation is derived from matching the constructed and fitted tooth surfaces. Results show that, before and after PSE compensation, L300G tooth lead measuring accuracy is level 4; after PSE compensation, L300G tooth profile measuring accuracy is improved by 2 grades, reaching level 4, which is consistent with Gleason 350 GMS measuring report; fluctuation range of tooth surface morphology deviation is 0–5 μm, and the tooth profile error and tooth lead error extracted from morphology deviation are consistent with Gleason 350GMS measuring report. The model effectively enhances measuring accuracy, truly reflects the 3D morphology of grinded topological modification tooth surface, and fairly eliminates the limitation of incomplete evaluation of a single error measured item. It is expected to be popularized in high-precision measuring and grinding technology of horizontal or vertical gear grinders.